EMBRACING THE KNOWLEDGE: THE JOB TRAINING IN PERMANENT REFLECTIVE PHYSICAL EDUCATION SCHOOL TEACHERS. (Fiep Bulletin - online, 2014)
The study aims to identify the contributions that are assigned by the teachers of physical education to work on their reflective process of life history and training. The research was accomplished during the project Integrando Saberes na Formação Permanente em Educação Física Escolar promoted by the Instituto de Educação Física e Esportes da Universidade Federal do Ceará, in partnership with the Ministry of Education. The study was conducted through the Module Life history and Training, developed during the project, with a workload that corresponded to twenty hours, in which were discussed the historical, conceptual and experiential of the theme. Thirty one teachers participated in the module from Ceará's state network and Fortaleza's province network. The study follows a qualitative descriptive approach. For data collection questionnaire was used with three questions. We focused our work as a reference to the second question, which inquired teachers, about the contributions that can highlight the reflective work in permanent education / continuing education? The questionnaire was administered after the completion of the narrative. For a discussion of the results an analysis technique was used for the determination of categories. The collection showed two broad categories: a) The engagement of their own history, and b) the thought that teaching with a desire of possible change. The first category, the interlocutors indicated as a contribution of the narrative a moment of self-knowledge of the history, the importance of family and sharing of experiences, in the second, the story had a character of self-evaluation, search for solutions, motivation, useful for possible changes. It was possible to see the potential of critical reflection in lifelong learning, which was established from thinking about life experiences and training and educational opportunities to leverage this recognition, coping and overcoming the limit of the situation found in the professional and personal aspect
Keywords: physical education; reflexivity; life history.